2001
DOI: 10.1136/gut.49.5.720
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic portal vein thrombosis: aetiology and determinants of survival

Abstract: Background-Malignancy, hypercoagulability, and conditions leading to decreased portal flow have been reported to contribute to the aetiology of extrahepatic portal vein thrombosis (EPVT). Mortality of patients with EPVT may be associated with these concurrent medical conditions or with manifestations of portal hypertension, such as variceal haemorrhage. Patients and methods-To determine which variables have prognostic significance with respect to survival, we performed a retrospective study of 172 adult EPVT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
224
5
17

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(259 citation statements)
references
References 19 publications
13
224
5
17
Order By: Relevance
“…Although gastrointestinal bleed at diagnosis of PVT, (13) anticoagulant therapy, (25) extension of thrombosis to the splenic vein, presence of gastric fundal varices, (32) and thrombosis of the superior mesenteric vein (34) have all been described as predictive factors associated with rebleeding episodes during follow-up, we could not confirm these findings in our study. Finally, in our cohort of patients with PVT the mortality was very low, only occurring in nine patients (5%) with an actuarial probability of survival of 99% and 96% at 1 and 5 years, respectively, confirming the good prognosis of these patients.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Although gastrointestinal bleed at diagnosis of PVT, (13) anticoagulant therapy, (25) extension of thrombosis to the splenic vein, presence of gastric fundal varices, (32) and thrombosis of the superior mesenteric vein (34) have all been described as predictive factors associated with rebleeding episodes during follow-up, we could not confirm these findings in our study. Finally, in our cohort of patients with PVT the mortality was very low, only occurring in nine patients (5%) with an actuarial probability of survival of 99% and 96% at 1 and 5 years, respectively, confirming the good prognosis of these patients.…”
Section: Discussioncontrasting
confidence: 73%
“…Finally, in our cohort of patients with PVT the mortality was very low, only occurring in nine patients (5%) with an actuarial probability of survival of 99% and 96% at 1 and 5 years, respectively, confirming the good prognosis of these patients. (13,25,33,35) In our study, by univariate Cox regression analysis, age, altered liver enzymes, and ascites were significantly associated with mortality, as observed by Janssen et al (25,34) and Orr et al (33) In this study, selection bias was minimized by including all patients with noncirrhotic, nontumoral PVT registered and followed at the two centers. The long study period of over 20 years could be associated with a change in the management of patients seen early in the study compared to those diagnosed more recently, with the latter patients being more likely to receive anticoagulation and consequently a greater possibility of portal vein recanalization.…”
Section: Discussionsupporting
confidence: 63%
“…17 A multivariate analysis done on determinants of survival in extra hepatic portal vein thrombosis showed that advanced age, malignancy, cirrhosis, mesenteric vein thrombosis, absence of abdominal inflammation, serum levels of aminotransferase and albumin are associated with reduced survival and not to complications of portal hypertension. 15 Chronic PVT did not show any extension of the thrombus as shown by repeat imaging after as long as 10 years. 114 Bleeding after initial variceal eradication occurs usually within first 4-10 years and the risk of bleeding reduces as age progresses especially after 10 years.…”
Section: Chronic Portal Vein Thrombosismentioning
confidence: 74%
“…[8][9][10][11][12][13] In some cases multiple prothrombotic factors may be associated in the development of PVT. [14][15][16] In one study one or more risk factors namely prothrombotic state or abdominal inflammation was present in 87% of patients. 17 Amongst the thrombophilic states, primary myeloproliferative disorders (MPD) are common in 30.5%.…”
Section: Acute Non-cirrhotic Portal Vein Thrombosis Procoagulant Statementioning
confidence: 98%
See 1 more Smart Citation